Improving access and continuity of care for homeless people: how could general practitioners effectively contribute? Results from a mixed study. Issue 11 (30th November 2016) - Jego, Maeva; Grassineau, Dominique; Balique, Hubert; Loundou, Anderson; Sambuc, Roland; Daguzan, Alexandre; Gentile, Gaetan; Gentile, Stéphanie
Abstract : Objectives: To analyse the views of general practitioners (GPs) about how they can provide care to homeless people (HP) and to explore which measures could influence their views. Design: Mixed-methods design (qualitative –> quantitative (cross-sectional observational) → qualitative). Qualitative data were collected through semistructured interviews and through questionnaires with closed questions. Quantitative data were analysed with descriptive statistical analyses on SPPS; a content analysis was applied on qualitative data. Setting: Primary care; views of urban GPs working in a deprived area in Marseille were explored by questionnaires and/or semistructured interview. Participants: 19 GPs involved in HP's healthcare were recruited for phase 1 (qualitative); for phase 2 (quantitative), 150 GPs who provide routine healthcare ('standard' GPs) were randomised, 144 met the inclusion criteria and 105 responded to the questionnaire; for phase 3 (qualitative), data were explored on 14 'standard' GPs. Results: In the quantitative phase, 79% of the 105 GPs already treated HP. Most of the difficulties they encountered while treating HP concerned social matters (mean level of perceived difficulties=3.95/5, IC 95 (3.74 to 4.17)), lack of medical information (mn=3.78/5, IC 95 (3.55 to 4.01)) patient's compliance (mn=3.67/5, IC 95 (3.45 to 3.89)), loneliness in practice (mn=3.45/5, IC 95 (3.18 to 3.72)) and time required for the doctor (mn=3.25, IC 95 (3 to 3.5)). From qualitative analysis we understood that maintaining a stable follow-up was a major condition for GPs to contribute effectively to the care of HP. Acting on health system organisation, developing a medical and psychosocial approach with closer relation with social workers and enhancing the collaboration between tailored and non-tailored programmes were also other key answers. Conclusions: If we adapt the conditions of GPs practice, they could contribute to the improvement of HP's health. These results will enable the construction of a new model of primary care organisation aiming to improve access to healthcare for HP.